Four decades of developmental dysplastic hip screening according to Graf: What have we learned? - Walter, Sebastian G.; Ossendorff, Robert; Yagdiran, Ayla; Hockmann, Jan; Bornemann, Rahel; Placzek, Sonja (Frontiers in Pediatrics, 2022)
Purpose: Sonographic hip examination according to Graf is widely accepted standard for diagnosing developmental dysplastic hips (DDH) but it is criticized for alleged intra- and interobserver variations. This review was conducted to evaluate whether objective quality criteria according to the Graf method are fulfilled within scientific literature. Methods: A systematic literature search on Pubmed was performed using the search string: ((DDH) OR (Hip dysplasia)) AND (Graf)”. Studies suitable by title, abstract, manuscript, containing an image of sonographic hip examination and online accessibility were included into analysis. Results: 131 studies were included into final analysis. Only 68 presented correct sonographic images according Graf’s criteria. 98 studies plotted alpha-angles (angle between bony roof line and base line) but only 85 studies beta-angles (angle between cartilage roof line and base line). Studies were contributed from 25 countries. Conclusion: Assumingly, skepticism regarding the Graf method is based on user errors and insufficient application of the Graf quality assessment algorithm resulting in high intra- and interobserver variations. When performed correctly, the Graf method is of high diagnostic value.